Metastatic Marvel: Unravelling a Rare Case of Mandibular Metastasis of Occult Adenocarcinoma of Lung - Jaishri S. Pagare; Vikrant Kasat; Pooja M. Ghorpade (Journal of Indian Academy of Oral Medicine and Radiology)
Metastasis to the oral cavity is uncommon, accounting for only about 1% of newly diagnosed oral malignancies, with the mandible being more frequently affected than the maxilla. These metastases typically occur in the mandibular body and ramus, and their unusual clinical and radiographic presentations make diagnosis difficult. Breast, lung, kidney, and prostate cancers are the most common primary sources of jaw metastases. Clinical symptoms include pain, swelling, ulceration, loose teeth, trismus, and lymphadenopathy, though some cases are asymptomatic. This case report details a 65-year-old woman with bilateral mandibular swelling, later diagnosed as lung adenocarcinoma metastasizing to the mandible, vertebrae, and other regions. The case emphasizes the importance of considering metastatic tumors in the differential diagnosis of unexplained facial swelling, especially in patients with a history of cancer.